Reappraisal of risk factors in neoplastic lesions of the cervix uteri - Rohilla, Minakshi; Gupta, Hem Prabha; Aggarwal, Anjoo (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Carcinoma of uterine cervix is most common cancer amongst women in developing countries and rates the second most common cancer in women throughout the world. Despite possible correlation with factor like age, sexual activity, multiparity, smoking, alcohol, oral contraception and low socio economic status, suggested by various researchers, the exact role and a true causal association between these factors and carcinoma cervix has not been proved as yet. Methods: Two hundred and fiftyfour (254) patients with cervical lesions were screened for carcinoma of the cervix and 195 were found to be suffering from malignant and intraepithelial lesions. 59 patients had benign lesion of the cervix. Results: The commonest risk factor encountered in the study was early age at intercourse (84.25%) followed by multiparity (64.56%), illiteracy (64.56%), sexually transmitted disease (61.02%), bad hygiene (43.70%), low socio-economic class (42.91%), and tobacco use in decreasing order. These factors have complex interrelationship with each other e.g. low socioeconomic status is commonly associated with bad hygiene, illiteracy, multiparity and early age at first intercourse (p<0.001). Conclusions: Early detection of benign lesions and decrease in number of risk factors in an individual being minimum at lower age is probably associated with benign part of the spectrum of disease while constant presence of these factors leads to cervical intraepithelial neoplasia followed by truly invasive disease. Intervention at any point with decrease of or absence of risk factors can stop these premalignant lesions to become malignant.